PERANCANGAN APLIKASI DASHBOARD DATA MASYARAKAT MISKIN DI DESA MACANG SAKTI KABUPATEN MUSI BANYUASIN - Deni Nurdiansyah; Joni Karman; Muhammad Nur Alamsyah (JURNAL ILMIAH BETRIK, 2022)
In building and designing a data dashboard application for the poor in Macang Sakti Village, Musi Banyuasin Regency which can process data for the poor so that a data processing process can be even more effective. Building a data dashboard application for the poor that can quickly and effectively produce data on poor people and the resulting information can be used by the Village Head of Macang Sakti as a basis for making decisions that can improve services to the poor in Macang Sakti Village. The method used is the development life cycle method which is carried out by designing a dashboard application for the data of the poor in Macang Sakti village, Musi Banyuasin Regency to conduct testing first with the results obtained that the application is feasible to use and the system being tested is appropriate and successful as desired, so this application, it is feasible, to use. In the application of the development life cycle method and a complete application, it can make it easier for the government to check the data of the poor in Macang Sakti Village, Musi Banyuasin Regency.